Valorization of Citrus reticulata Blanco Peels to Produce Enriched Wheat Bread: Phenolic Bioaccessibility and Antioxidant Potential - Esther Gómez-Mejía; Iván Sacristán; Noelia Rosales-Conrado; María Eugenia León-González; Yolanda Madrid (MDPI AG, 2023)
The fortification of foods with bioactive polyphenols aims to improve their functional properties and to provide health benefits. Yet, to exert their benefits, phenolic compounds must be released from the food matrix and absorbed by the small intestine after digestion, so assessing their bioaccessibility is crucial to determine their potential role. This work aims to incorporate Citrus reticulata Blanco peel extracts into wheat bread as a promising opportunity to increase their bioactive potential, along with supporting the sustainable management of citrus-industry waste. A control and a wheat bread enriched at 2% and 4% (w/v) with a phenolic extract from mandarin peels were prepared and analyzed for antioxidant activity and phenolic composition using LC-MS and UV-Vis spectrophotometry. In addition, in vitro digestion was performed, and the digested extracts were analyzed with HPLC-MS/MS. The results showed a significant increase in total flavonoid content (TFC, 2.2 ± 0.1 mg·g−1), antioxidant activity (IC50 = 37 ± 4 mg·g−1), and contents of quercetin, caffeic acid, and hesperidin in the 4% (w/v) enriched bread. Yet, most polyphenols were completely degraded after the in vitro digestion process, barring hesperidin (159 ± 36 μg·g−1), highlighting the contribution of citrus enrichment in the development of an enriched bread with antioxidant potential.